Isolation and identification of halophilic bacteria producing halotolerant protease - Abd Samad, Nadiah Syuhada; Amid, Azura; Jimat, Dzun Noraini; Ab. Shukor , Nurul Aqilah (2015)
Proteases are known as one of the important groups of enzymes that have been used widely in various industries. However, high production cost of proteases in term of energy used for sterilization and high risk of microbial contamination during fermentation become the obstacles during upstream processing. Moreover, proteases that capable to withstand with harsh conditions of salinity, temperature and pH are required in industry. Therefore, this study presents newly isolated halophiles bacteria producing halotolerant proteases. Halophiles bacteria were isolated from fermented food. Screening of the bacteria producing halotolerant protease enzymes was carried out by using skim milk salt agar containing 10% NaCl at pH 7 and incubated under aerobic condition at 37oC for 2 days. The selected isolates were identified based on their morphological followed by 16S rDNA gene sequence analysis. 40 colonies of halophiles bacteria were isolated, however, only 20 of them showing proteolytic activity. All of 20 isolates are motile and gram positive bacteria. From 20 isolates, only 6 were chosen for further analysis. B7 showed the highest proteolytic activity compared with others. Results of 16S rDNA gene sequence analysis showed 98% homology to Bacillus amyloliquefaciens subsp. plantarum strain FZB42. Therefore, B7 is identified as Bacillus amyloliquefaciens strain B7.